Tsunami’s trail on spending: exploring gender differential impact in the aftermath of the 2004 disaster - Sengupta, Sagarika (2023)
This study delved into the aftermath of the 2004 tsunami, focusing on its gender-specific impact on consumption expenditure in India. The study used a Difference-in-Difference (DiD) approach, comparing expenditure patterns between the tsunami affected and unaffected districts of India for male-headed households, female-headed household and expenditure on male, female and adult goods. The data was drawn from the National Sample Survey Organisation (NSSO) Consumer Expenditure Survey, providing insights into Monthly Per Capita Consumption Expenditure (MPCE) and overall consumption expenditure across specific male and female goods. The results highlights a distinct gender-related dimension to the impact of the tsunami. Male headed households experienced a reduction in MPCE, revealing the vulnerability of their economic well-being in the face of such disasters. As a result, the study aims to find out if that led to gender-bias within households and had any impact on female goods. I find that there was a significant impact on women’s clothing, personal care sanitary products and adult goods. Although there has been a rise in expenditure on women’s clothing, but there has also been a decline in spending on sanitary products and adult goods, indicating mixed results. This nuanced perspective sheds light on the gender differentiated effects of natural calamities on consumption spending.